2,6-Diamino-4-(4-chlorophenyl)-1-methyl-1,4-dihydropyridine-3,5-dicarbonitrile - Purushothaman, Michael; Thanigaimani, Kaliyaperumal; Arshad, Suhana; Silambarasan, Sekar; Razak, Ibrahim Abdul; Ali, Kather Mohideen Sithick (International Union of Crystallography, 2014)
In the title compound, C14H12ClN5, the dihydropyridine ring adopts a shallow boat conformation. The dihedral angle between the plane of this ring and that of the chlorobenzene ring is 69.15 (15)o. In the crystal, molecules are linked by N—H...N and N—H...Cl hydrogen bonds, generating (001)sheets.